Determining the Optimal Fire Station Locations in Baghdad Al-Rusafa Using GIS Models and Data - AL-Aarajy, Khalid H. Abbas; Albakry, Sundus A. Abdullah (Iraqi Journal of Science, 2024)
The study of sitology has a long historical background and has recently attracted the attention of many researchers. One of its most important branches is the location of fire stations, which are of great importance in major cities. One of the most important features of an appropriate location is increasing coverage and reducing access time. In this research, geographic information systems were used to choose the most appropriate sites on the Al-Rasafa side in the city of Baghdad/Iraq to facilitate access to the scene of the accident as soon as possible from the fire stations and through the use of the geographical database of the city of Baghdad. GIS analysis was used to build the mathematical model that was adopted based on a number of criteria, including land use, distance to commercial malls, government and educational institutions, hospitals, and distance from existing fire stations. A weight was given to each of these criteria using the Overlay Weighted tool from spatial analysis in geographic information systems to determine the most appropriate areas. Then the road network was added to the criteria used, and then the selection was made on the areas close to the main roads, so the search results were to determine the best sites in Al-Karrada, Al-Sadr City, and Al-Adhamiya.